Nazis the occult conspiracy - Atkinson, Tracy 1928-.; Baran, Joan.; Shane, Lester; McDowell, Malcolm 1943-.; Annabar Pictures, Inc.; Discovery Channel (Firm).; Discovery Channel Video (Firm).; Magna Vision (Bethesda, Md. distributed by Discovery Channel Video ; distributed in the Philippines by MagnaVision, 2002)
Nazism was no mere political movement as is commonly believed, rather. it was an occult religion in which Adolf Hitler was the messiah, Heinrich Himmler the high priests and the SS Death Head Formation, the clergy. This film documents the Third Reich's use of the occult in an effort to help them win World War II. The Reich used the mystical arts to make important battle decisions, train SS officers, indoctrinate the German public and to try and influence the Allies. Through montage, Nazi symbols are compared with carvings of the magical Nordic Runic alphabet, and archival footage of Nazis dressed as medieval knights, demonstrating Nazi's attempted to breed a "purified" race of Aryan god-men and annihilated the "impure" to fullfill their horrifying ideology. Contains interviews with those who experienced the Nazi occult.
Co-producer/director of photography, Mark Hubatsek ; music composed by Elizabeth Swados ; edited by Deborah Barkow, Hiro Kay, Tom McArdle.
Narrated by Malcolm McDowell.
VCD
Keywords: Occultism -- Germany; Holocaust, Jewish (1939-1945)